Food science and COVID-19 (2020)
Theories proposing a role of specific dietary components or food supplements in the prevention or treatment of COVID-19 have received extensive social media coverage. A multitude of scientific publications have also pointed to the importance of food and nutrition in combating the COVID-19 pandemic. The present perspective critically addresses the question of what food science can actually contribute in this context. Animal studies suggest that micronutrients, food bioactives or functional foods may carry the potential to augment viral defense. However, the specific roles of food components in viral infectious diseases in humans remain unclear. Rigorous research assessing the efficacy of food compounds in counteracting infections would require long-term randomized controlled trials in large samples. While no foods, single nutrients or dietary supplements are capable of preventing infection with COVID-19, a balanced diet containing sufficient amounts of macronutrients and diverse micronutrients is a prerequisite of an optimally functioning immune system. Highenergy diets and obesity are major risk factors for a more severe course of COVID-19. Therefore, population-wide body weight control and weight reduction in overweight people are important preventive measures. Diet may play a beneficial role in maintaining a healthy body weight and preventing non-communicable conditions.